Application of Blended Learning on Arabic Language Learning during the Covid-19 Pandemic 4th grade in Elementary School - Novia Lu’lu’ul Muniroh; Najih Anwar (Universitas Muhammadiyah Sidoarjo, 2022)
The obstacles to learning during the covid-19 pandemic were especially limited to fourth-grade Arabic learning at muhammadiyah elementary school. 11 randegan. This article aims to identify the process, the contributing factors and the retardential factors in the learning of arabic. 11-randegan class 4 student student at muhammadiyah elementary school. The methods used are descriptive qualitative methods using methods of observation, interview, and documentation. Efforts made that the process of applying blended learning to Arabic learning are three stages: the process of planning, implementation and evaluation. As for the supporting factors of teachers and technology, while the inhibitory factors of Internet connection, short time and lack of student motivation.